Effect of Tactile Stimulation on Termination and Prevention of Apnea of Prematurity: A Systematic Review - Cramer, Sophie J. E.; Dekker, Janneke; Dankelman, Jenny; Pauws, Steffen C.; Hooper, Stuart B.; te Pas, Arjan B. (Frontiers in Pediatrics, 2018)
Apnea of prematurity (AOP) is one of the most common diagnoses in preterm infants. Severe and recurrent apneas are associated with cerebral injury and adverse neurodevelopmental outcome. Despite pharmacotherapy and respiratory support to prevent apneas, a proportion of infants continue to have apneas and often need tactile stimulation, mask, and bag ventilation and/or extra oxygen. The duration of the apnea and the concomitant hypoxia and bradycardia depends on the response time of the nurse. We systematically reviewed the literature with the aim of providing an overview of what is known about the effect of manual and mechanical tactile stimulation on AOP. Tactile stimulation, manual or mechanical, has been shown to shorten the duration of apnea, hypoxia, and or bradycardia or even prevent an apnea. Automated stimulation, using closed-loop pulsating or vibrating systems, has been shown to be effective in terminating apneas, but data are scarce. Several studies used continuous mechanical stimulation, with pulsating, vibrating, or oscillating stimuli, to prevent apneas, but the reported effect varied. More studies are needed to confirm whether automated stimulation using a closed loop is more effective than manual stimulation, how and where the automated stimulation should be performed and the potential side effects.